Biometric recognition : 12th Chinese Conference, CCBR 2017, Shenzhen, China, October 28-29, 2017, Proceedings /: 12th Chinese Conference, CCBR 2017, Shenzhen, China, October 28-29, 2017, Proceedings. (2017) - Unknown
No abstract available